Thermal characterisation of a lightweight mortar containing expanded perlite for underground insulation. (25th July 2011) - Liu, W.V.; Apel, D.B.; Bindiganavile, V.
This paper aims to investigate the use of expanded perlite in mortar, for further application of shotcrete to thermal insulation of underground mines. Mixes were designed according to the typical proportions of underground shotcrete, with the sand volumetrically substituted by expanded perlite. Tests of samples were conducted at four ages. Transient plane source technique was utilised to measure the thermal properties. The results showed reduced weight, decreased thermal conductivity, deteriorated thermal diffusivity, and sacrificed mechanical strength with perlite addition. Experimental data analysis and explanation in this paper would establish useful fundamentals for further application of expanded perlite to underground shotcrete.